1977
DOI: 10.1161/01.res.41.6.849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acidosis and ischemia on contractility and intracellular pH of rat heart.

Abstract: SUMMARY The effects of respiratory and metabolic acidosis on myocardial contractility and energy production have been investigated in the perfused rat heart. Respiratory acidosis, produced by increasing the Pco 2 , caused an 80% inhibition of pressure development at pH 6.7. When artificial buffers (plus HCI) were used in place of bicarbonate and CO 2 , only a 30% inhibition of pressure development was observed at pH 6.7. Respiratory acidosis produced a greater intracellular acidosis than artificial buffer acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(115 citation statements)
references
References 43 publications
7
106
1
Order By: Relevance
“…Indeed, the data of Steenbergen et al [13] suggests that the rise in phi seen in the present studies would, if taking place in the absence of other factors, have produced a significant positive inotropic effect. The cause of the relative hypotension in the alkalitreated groups remains to be conclusively demonstrated.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Indeed, the data of Steenbergen et al [13] suggests that the rise in phi seen in the present studies would, if taking place in the absence of other factors, have produced a significant positive inotropic effect. The cause of the relative hypotension in the alkalitreated groups remains to be conclusively demonstrated.…”
Section: Discussionsupporting
confidence: 47%
“…Specifically, this appears to be the case for the negative inotropic effect of systemic acidosis [13,14] and for the inhibition of hepatic gluconeogenesis from lactate [15,16]. It is therefore a testable hypothesis that therapies which correct intracellular acidosis are advantageous in haemodynamic and metabolic terms.…”
mentioning
confidence: 99%
“…External Mg2" inhibits the outward exchange current more effectively than the inward exchange current, indicating that Mg2`interacts preferentially with the Ca2" binding (Kimura, 1996). On the other hand, inhibition of quinaqurine is similar to amiloride derivatives (De La Pefia & Reeves, 1987 It has been hypothesized that cardiac ischaemia causes intracellular acidosis due to anaerobic metabolism (Steenbergen et al, 1977;Allen & Orchard, 1987) and ATP hydrolysis (Dennis et al, 1991). As a consequence, the Na+ /H+ exchange system is activated and causes Na+ influx and H+ efflux (Frelin et al, 1984;Poole-Wilson, 1989).…”
Section: Electrophysiological Experimentsmentioning
confidence: 99%
“…[20][21][22][23][24] Walley et al reported that hypercapnic acidosis (PaCO 2 92 mmHg) decreases Ees by 19% in dogs anesthetized with fentanyl. 2 5 In contrast to previous studies in humans or dogs, hypercapnic acidosis caused bradycardia and reduced CO in our study of rabbits.…”
Section: Discussionmentioning
confidence: 99%